CHOCOLATE COOKING - Gill, Cathy, author 641839 (London : Octopus, 1984)
Cathy Gill has produced a chocaholic's dream, a wnole book full of delicious, heavenly chocolate treats to delight the senses. Every taste is catered for with her elegant puddings, mouthwatering souffl?s and stunning cakes. Amaze your guests with her fabulous chocolate g?teaux, sufficiently grand and impressive to grace any p?tisserie. Delight the small fry with her spectacular animal fantasy cakes - birthday teas will never be the same again - and earn kudos as a provider of yummy chocolate fudge, toffee, ice cream and fruit splits. Cathy Gill is an experienced home economist who has worked for both the Gas Board and the Prestige Group. She also lectures as a cookery demonstrator and trains students in recipe development. Illustrated in full colour throughout with many clear step-by-step diagrams.